"Make Sure You See This": Counternarratives of Multilingual Black Girls' Language and Literacy Practices. (November 2021) - Presiado, Vivian E.; Frieson, Brittany L.
Critical scholarship in bilingualism and bilingual education has documented multiple ways that the rich language and literacy practices of Black children participating in bilingual education programs are often erased in favor of dominant narratives about the literacy practices of their White Mainstream English–speaking peers. Utilizing Black girl literacies, raciolinguistics, and translanguaging as theoretical orientations, and counternarratives as an analytical tool, this article presents a cross-case analysis of two ethnographic case studies that explored how multilingual Black American girls enrolled in an elementary dual-language bilingual education program employed their literacies to navigate their social worlds by challenging raciolinguistic ideologies and hegemonic systems of oppression in their daily lives. It also presents the nuanced nature of multilingual Black girls' literacies and the various roles that they serve, which are often ignored in multilingual spaces. The need to learn from multilingual Black girls' counternarratives is emphasized by engaging in a deeper sociopolitical understanding of the complex issues that Black girls face on a regular basis, which are often extended in bilingual spaces. Specifically, we call for educators to create critical translanguaging spaces that honor multidimensional counternarratives and intimately connect with the unique epistemologies and literacies that Black girls in bilingual programs bring to the table.